Cross-linked torlon/P84 hollow fiber membranes for highly selective NH3 separation with enhanced stability - Chang-In Kong; Myeong-Hun Hyeon; Hyeon-Jin Cho; Chae-Young Park; Taehoon Kim; Jong Geun Seong; Cheol Park; Jae-Hyeok Lee; Chang-Ha Lee; Su-Young Moon (Chemical Engineering Journal, 2026)

A method for identifying revisions in ship drawings using change detection and synthetic revision generation - In-Su Han; Myung-Il Roh; Min-Chul Kong; Seong-Won Choi; Hwasup Jang; Yeonhwa Jo; Gapheon Lee (Ocean Engineering, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Reducing greenhouse gas emissions while improving rice yield and water use efficiency in rice paddies through mid-season drainage and intermittent irrigation - Su-Heon Jang; Jae-In Lee; Chang-Gu Lee; Gil Won Kim; Jin-Kyung Hong; Seong-Jik Park (Agriculture, Ecosystems & Environment, 2026)

Heavy metals in carbonated waters and beverages on the South Korean market - Yongcheol Lee; Hyuny Clark-Shim; Min-Su Chang; In-Sook Lee; Yun-Jung Yi; Hyun-Jeong Kim (Food Additives & Contaminants Part B-Surveillance, 2026)

Trait–environment diagnosis of ecological instability in Korean streams using benthic diatoms and machine learning: a UMAP–CDI framework - Jun-Ho Lee; Hyo Gyeom Kim; Byeong-Hun Han; In-Hwan Cho; Ha-Kyung Kim; Eun-A. Hwang; Su-Ok Hwang; Baik-Ho Kim (Aquatic Sciences, 2026)

Functional characterization and enhanced production of extracellular vesicles from lactic acid bacteria using red light-emitting diodes - Su Yeon Park; Hyun Jin Na; In-Geun Jung; Do Yup Lee; Yeong Ji Oh (Biocatalysis and Agricultural Biotechnology, 2026)

Cultivar-dependent peel browning in oriental melon is associated with surface protection and stress response regulation during storage - Me-Hea Park; Tae-Yeong Ko; Kang-Mo Ku; Kyung Ran Do; Sang-Mo Kang; Jinsu Lee; Hyang-Lan Eum; Hyo In Yoon; Su-Hyun Choi; Gyu Hyeon Park; Siva Kumar Malka (Postharvest Biology and Technology, 2026)

Development of Novel Host-Associated Low-Temperature Probiotics (HALP) Tailored to Aquaculture Applications - Su-Jeong Lee; Young-Sun Lee; Yu-Ri Kim; Mi-Hyeon Jeon; Da-In Noh; Seong-Mok Jeong; Kang-Woong Kim; Eun-Woo Lee; Won Je Jang (Probiotics and Antimicrobial Proteins, 2026)

First report of Diaporthe nobilis causing trunk canker on Quercus myrsinifolia Blume (evergreen oaks; Fagaceae) in Korea - Vantha Choub; Ju-Yeol Yun; Su-In Choi; Su-Yeon Lee; Jae-Hyun Moon; Henry B. Ajuna; Eun-Young Yim; Young Sang Ahn (Journal of Plant Pathology, 2026)

Calcium carbonate hybrid microcomposite for oral delivery of luteolin, a poorly water-soluble phytocompound - Jung-Ki Hong; Yeji Kang; Seong-Wook Seo; Ji-Su Kong; Gayeong Lee; Chan Hee Lee; Jongwook Jeong; Ee Taek Hwang; In-Soo Yoon (Food Chemistry, 2026)

Development of an aptamer-based diagnostic method targeting PRRSV-induced cytopathic effects - In-Hwan Oh; Phat-Loc Nguyen; Dae-Young Park; Jin-Pyo Lee; Woo-Ri Shin; Su-Min Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2026)

Anti-inflammatory effect of a Capsosiphon fulvescens (Chlorophyta) extract obtained by subcritical water extraction on lipopolysaccharide-induced RAW 264.7 cells - Ju-Hye Im; Su-mi Park; Yu-Jin Heo; Mi-Kyung Lee; Hae-In Lee (Journal of Applied Phycology, 2026)

A monolithic Janus dural sealant with adhesive and lubricant surfaces activated by non-toxic visible light exposure - Subin Kang; Hyeseon Lee; Sijoon Lee; Keum-Yong Seong; Yeon Suk Song; Ji-Su Kong; Yeji Kang; Kyoick Koo; Hak Mo Sung; In-Soo Yoon; Kyoung Hyup Nam; Seung Yun Yang (Chemical Engineering Journal, 2026)

Enhancing CO2-to-CH4 conversion efficiency of TiO2 through synergistic morphology tuning, defect engineering, and heterojunction formation - Dongyun Kim; Kyuseok Lee; Young Ho Park; Junho Lee; Jeonghyeon Lee; Chaelin Shin; Hyeonjong Jeong; Chang-Hee Cho; G. Murali; Seung Jun Lee; Insik In; Su-Il In (Chemical Engineering Journal, 2026)

Disturbance of benthic topography and macrofauna community by sand mining in EEZ of the South Sea of Korea - Dong-U Kim; Changkeun Lee; Su In Kim; Seong Woon Jeong; Taeha Kim; Eun Pyo Lim; Soonwoo Lee; Soonyoung Wang; Seong Eun Kim; Jong Seong Khim; Ho Kyung Ha (Regional Studies in Marine Science, 2025)

Characterization and comparative analysis of saponins in various spinach (Spinacia oleracea L.) cultivars according to growing seasons - Su-Yeon Lee; Doo-Young Kim; Hyun-Jae Jang; Seon Min Oh; Hyoung-Geun Kim; Jongmin Ahn; In-Seo Heo; Heung Joo Yuk; Eun Kyoung Seo; Sei-Ryang Oh; Hyung Won Ryu (Food Chemistry, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

Collagenase and tyrosinase inhibitory compounds from fish gut bacteria Ruegeria atlantica and Pseudoalteromonas neustonica - Jonghwan Kim; Su Jung Hwang; Gyu Sung Lee; Ju Ryeong Lee; Hye In An; Hong Sik Im; Minji Kim; Sang-Seob Lee; Hyo-Jong Lee; Chung Sub Kim (Phytochemistry Letters, 2025)

Study on modulation of inflammation expression by Brassica oleracea L. leaves extract - Jung-Wook Kang; Dan-Hee Yoo; Hyo-Min Kim; Ji-Won Hur; Kyeung-A Kwon; Kyung-Eun Lee; Min-Yeong Kim; Yong-Jun Kwon; Su-Bin Yu; Ju-Hyun Park; In-Chul Lee (Phytochemistry Letters, 2025)

Floral development and phenolic compounds production in Agastache rugosa through light regulation - Yun Ji Park; Su Hyeon Lee; Hyo In Yoon; Jai-Eok Park; To Quyen Truong; Je Hyeong Jung; Jung-Seok Yang; Inkyu Park; Sang Min Kim (Planta, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Green utilization of Meretrix lusoria shell for phosphorus removal, pathogenic bacteria inactivation, and phosphorus supply for crop growth - Su-Heon Jang; Jae-In Lee; Chuluuntsetseg Jadamba; Heejin Yang; Chang-Gu Lee; Soo-Cheul Yoo; Seong-Jik Park (Journal of Water Process Engineering, 2025)

Effect of mealworm component and extrusion temperature on fibrous structure formation and physicochemical properties of meat analog extrudates - Chhychhy Chao; Jang Hong Lee; Hyun Woo Kim; In Woo Kim; Hyun Jin Park; Su Hyun Lee (Food Chemistry, 2025)

A representation method of pipe connections and routing space in pipe auto-routing using graph and octree structures - Min-Chul Kong; Myung-Il Roh; In-Su Han; Inseok Lee; Hyunseung Lee; Mijin Kim; Jeoungyoun Kim; Jinhyeong You (Ocean Engineering, 2025)

Continuous manufacturing and process analytical technology: focusing on dosage forms with improved solubility and controlled release - Su Hyun Seok; Seung-Dong Yoo; Dong‑Wook Kim; In-Ah Lee; Kyung Hyun Min; Ji-Hyun Kang; Chun-Woong Park; Ju-Young Kim; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2025)

Plastid-nuclear coevolution of ribosomal protein genes in papilionoid legumes - Lydia G. Tressel; Bikash Shrestha; Chaehee Lee; In-Su Choi; Tracey A. Ruhlman; Domingos Cardoso; Martin F. Wojciechowski; Robert K. Jansen (Molecular Phylogenetics and Evolution, 2025)

Chitosan-gallic acid conjugate edible coating film for perishable fruits - Cho Rok Lee; Su Jin Lee; Tae In Kim; Kiramage Chathuranga; Jong Soo Lee; Sangsik Kim; Min Hee Kim; Won Ho Park (Food Chemistry, 2025)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Evaluation of large-scale poultry manure-derived biochar for efficient cadmium removal in zinc smelter wastewater - Jae-In Lee; Su-Heon Jang; Changsup Kim; Jin-Kyu Kang; Chang-Gu Lee; Seong-Jik Park (Journal of Environmental Management, 2024)

Crystalline carbon antioxidase mimics enhancing innate anti-inflammatory immunity for the treatment of rheumatoid arthritis - Chanhee Choi; DaBin Yim; Hyo Keun Kim; Su-Ji Jeon; In-Jun Hwang; Hongwon Kim; Yoonhee So; Sin Lee; Yejoo Yu; Yujin Choi; Hwankyu Lee; Chul-Su Yang; et al. (Chemical Engineering Journal, 2024)

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

T cell receptor clonotype in tumor microenvironment contributes to intratumoral signaling network in patients with colorectal cancer - In Hye Song; Seung-been Lee; Byung-Kwan Jeong; Jungwook Park; Honggeun Kim; GunHee Lee; Su Min Cha; Heejae Lee; Gyungyub Gong; Nak-Jung Kwon; Hee Jin Lee (Immunologic Research, 2024)

99mTc-DMSA and 99mTc-DTPA identified renal dysfunction due to microplastic polyethylene in murine model - Javeria Zaheer; Joycie Shanmugiah; Seungyoun Kim; Hyeongi Kim; In Ok Ko; Byung Hyun Byun; Myeong A Cheong; Seung-Sook Lee; Jin Su Kim (Chemosphere, 2024)

Exploratory data analysis of the correlation between bioactive components in various tea extracts and the digestive function in vitro - Kang-Woo Lee; In-Su Na; Dong-Ho Lee; Jin-Woo Kim; Na-Yeon Lee; Jin-Oh Chung; Hyun Woo Jeong; Jonghee Sohn; Wan-Gi Kim; Soon-Mi Shim (Food Bioscience, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Distributions of PCDD/Fs, PCBs, and PCNs in coastal sediments collected from major industrial bays in South Korea - Ji-Young Son; Sanjenbam Nirmala Khuman; Min-Kyu Park; Ho-Young Lee; Chul-su Kim; In-Seok Lee; Sung-Deuk Choi (Marine Pollution Bulletin, 2024)

Dynamic Ti3+ and In3+ dual active sites on In2TiO5 to enhance visible-light-driven gas-phase photocatalytic CO2 reduction - Niket S. Powar; Myeongjin Jang; Min Gyu Kim; Chaitanya B. Hiragond; Junho Lee; Eunhee Gong; Hwapyong Kim; Dongyun Kim; Jin-Woo Jung; Chang-Hee Cho; Tierui Zhang; Minho Kim; et al. (Chemical Engineering Journal, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Multilayer composite membranes composed of carbon molecular sieve membranes sandwiched between stacked zeolite nanosheets - Dong Yun Han; Ah Hyun Lee; Su Kyung Kang; Se Wan Kim; Woo Chul Kwak; In-Seok Jeon; Seunghwa Yang; Pyung Soo Lee (Chemical Engineering Journal, 2024)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Tannic acid-assisted in-situ interfacial formation of Prussian blue-assembled adsorptive membranes for radioactive cesium removal - Sung-Joon Park; Seung Su Shin; Joon Hee Jo; Chan Hee Jung; Hosik Park; You-In Park; Hyung-Ju Kim; Jung-Hyun Lee (Journal of Hazardous Materials, 2023)

High-flux CO2 separation using thin-film composite polyether block amide membranes fabricated by transient-filler treatment - Chae-Young Park; Chang-In Kong; Eun-Young Kim; Chang-Ha Lee; Ki-Suk Kim; Jae-Hyeok Lee; Jongmyeong Lee; Su-Young Moon (Chemical Engineering Journal, 2023)

Double-blind randomized placebo-controlled study of the efficacy and safety of hair loss prevention shampoo containing salicylic acid, panthenol, and niacinamide in alopecia patients - Hee-Taek Kim; Hye-Su Park; Yong-Min Kim; In-Chul Lee; Sang-Jun Lee; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2022)

Essential oil from Chrysanthemum boreale flowers modulates SNARE protein-linked mast cell response and skin barrier proteins and ameliorates atopic dermatitis-like lesions in mice - Do Yoon Kim; Kyung-Jong Won; Dae Il Hwang; Su Yeon Lee; In-Ho Choi; Bokyung Kim; Hwan Myung Lee (Horticulture, Environment, and Biotechnology, 2022)

Anti-inflammatory activity of palmitoylethanolamide ameliorates osteoarthritis induced by monosodium iodoacetate in Sprague–Dawley rats - Jae In Jung; Hyun Sook Lee; Young Eun Jeon; So Mi Kim; Su Hee Hong; Joo Myung Moon; Cho Young Lim; Yoon Hee Kim; Eun Ji Kim (Inflammopharmacology, 2021)
Novel treatment strategies are urgently required for osteoarthritis (OA). Palmitoylethanolamide (PEA) is a naturally occurring fatty acid amide with analgesic and anti-inflammatory effects. We aimed to examine its effect on OA and elucidate the molecular mechanism of actions in monosodium iodoacetate (MIA)-induced OA Sprague–Dawley rats. The experimental animals were divided into normal control group (injected with saline + treated with phosphate-buffered saline (PBS), NOR), control group (injected with MIA + treated with PBS, CON), 50 or 100 mg/kg body weight (BW)/day PEA-treated group (injected with MIA + treated with 50 or 100 mg of PEA/kg BW/day, PEA50 or PEA100), and positive control group (injected with MIA + treated with 6 mg of diclofenac/kg BW/day, DiC). The changes in blood parameters, body parameters, gene expression of inflammatory mediators and cytokines, knee thickness, and joint tissue were observed. Oral administration of PEA had no adverse effects on the BW, liver, or kidneys. PEA reduced knee joint swelling and cartilage degradation in MIA-induced OA rats. The serum levels of leukotriene B4, nitric oxide, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and prostaglandin E2 considerably reduced in the PEA100 group compared with those in the CON group. In the synovia of knee joints, the mRNA expression of iNOS , 5-Lox , Cox-2 , Il-1β , Tnf-α , and Mmp-2 , -3 , -9 , and -13 apparently increased with MIA administration. Meanwhile, Timp-1 mRNA expression apparently decreased in the CON group but increased to the normal level with PEA treatment. Thus, PEA can be an effective therapeutic agent for OA.

University of Washington Nathan Shock Center: innovation to advance aging research - Matt Kaeberlein; Alessandro Bitto; Maitreya J. Dunham; Warren Ladiges; Su-In Lee; Michael J. MacCoss; Alexander Mendenhall; Daniel E. L. Promislow; Peter S. Rabinovitch; Judit Villén; Lu Wang; Yuliang Wang; et al. (GeroScience, 2021)

Determination of 12 herbal compounds for estimating the presence of Angelica Gigas Root, Cornus Fruit, Licorice Root, Pueraria Root, and Schisandra Fruit in foods by LC-MS/MS - Su-Jin Ahn; Hyung Joo Kim; Ayoung Lee; Seung-Sik Min; Sangwhan In; Eunmi Kim (Food Additives & Contaminants: Part A, 2020)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Rice CaM-binding transcription factor (OsCBT) mediates defense signaling via transcriptional reprogramming - Jung-Sung Chung; Sung Cheol Koo; Byung Jun Jin; Dongwon Baek; Seon-In Yeom; Hyun Jin Chun; Man Soo Choi; Hyun Min Cho; Su Hyeon Lee; Wook-Hun Jung; Cheol Woo Choi; Anil Kumar Nalini Chandran; et al. (Plant Biotechnology Reports, 2020)

Effects of the DNA repair inhibitors, cytosine arabinoside and 3-aminobenzamide, on the frequency of radiation-induced micronuclei, nuclear buds, and nucleoplasmic bridges - Yoon Hee Cho; Yang Jee Kim; Sunyeong Lee; Kyung-in Joung; Hai Won Chung; Sunmi Kim; Su Young Kim (Genes & Genomics, 2020)

Integration of transcriptomics, proteomics and metabolomics identifies biomarkers for pulmonary injury by polyhexamethylene guanidine phosphate (PHMG-p), a humidifier disinfectant, in rats - Jung Dae Lee; Hyang Yeon Kim; Keunsoo Kang; Hye Gwang Jeong; Mi-Kyung Song; In Hwan Tae; Su Hyun Lee; Hae Ri Kim; Kyuhong Lee; Sehyun Chae; Daehee Hwang; Suhkmann Kim; et al. (Archives of Toxicology, 2020)

Production of a Monoclonal Antibody Targeting the M Protein of MERS-CoV for Detection of MERS-CoV Using a Synthetic Peptide Epitope Formulated with a CpG–DNA–Liposome Complex - Byoung Kwon Park; Su In Lee; Joon-Yong Bae; Man-Seong Park; Younghee Lee; Hyung-Joo Kwon (International Journal of Peptide Research and Therapeutics, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

Production of Anti-c-Myc Monoclonal Antibody Inhibiting DNA Binding of c-Myc and Max Dimer by Epitope Peptide–CpG-DNA–Liposome Complex Without Carriers - Byoung Kwon Park; Avishekh Gautam; Sony Maharjan; Su In Lee; Younghee Lee; Hyung-Joo Kwon (International Journal of Peptide Research and Therapeutics, 2019)

Effects of three-dimensional spheroid culture on equine mesenchymal stem cell plasticity - Mi Jeong Park; Jienny Lee; Jeong Su Byeon; Da-Un Jeong; Na-Yeon Gu; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Evaluation of the 2.5-km Cloud-Resolving Storm Simulator in Predicting Local Afternoon Convection during the Summer in Taiwan - Chung-Chieh Wang; Nan-Chou Su; Jou-Ping Hou; Dong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Seismicity of the 2016 ML 5.8 Gyeongju earthquake and aftershocks in South Korea - Jimin Lee; Yonggyu Ryoo; Sun Cheon Park; Young Mo Ham; Jong Soo Park; Myeong Su Kim; Sang Mi Park; Hyen Geom Cho; Keun Su Lee; In Sun Kim; Hye Su Kim; Sunhee Bae (Geosciences Journal, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Intercomparison of Terrestrial Carbon Fluxes and Carbon Use Efficiency Simulated by CMIP5 Earth System Models - Dongmin Kim; Myong-In Lee; Su-Jong Jeong; Jungho Im; Dong Hyun Cha; Sanggyun Lee (Asia-Pacific Journal of Atmospheric Sciences, 2018)

Erratum to: Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Hymenobacter knuensis sp. nov., Isolated From River Water - Leonid N. Ten; Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Myung Kyum Kim; Hee-Young Jung (Current Microbiology, 2017)

Deinococcus knuensis sp. nov., a bacterium isolated from river water - Jae-Jin Lee; Yeon-Hee Lee; Su-Jin Park; Seung-Yeol Lee; Sangkyu Park; Dae Sung Lee; In-Kyu Kang; Leonid N. Ten; Hee-Young Jung (Antonie van Leeuwenhoek, 2017)

Resistance to pathologic cardiac hypertrophy and reduced expression of CaV1.2 in Trpc3-depleted mice - Jung Woo Han; Young Ho Lee; Su-In Yoen; Joel Abramowitz; Lutz Birnbaumer; Min Goo Lee; Joo Young Kim (Molecular and Cellular Biochemistry, 2016)

Genetic characteristics of highly pathogenic H5N8 avian influenza viruses isolated from migratory wild birds in South Korea during 2014-2015 - Young-Jae Si; Won Suk Choi; Young-Il Kim; In-Won Lee; Hyeok-Il Kwon; Su-Jin Park; Eun-Ha Kim; Se mi Kim; Jin-Jung Kwon; Min-Suk Song; Chul-Joong Kim; Young-Ki Choi (Archives of Virology, 2016)

Chondrogenic potential and anti-senescence effect of hypoxia on canine adipose mesenchymal stem cells - Jienny Lee; Jeong Su Byeon; Keum Sil Lee; Na-Yeon Gu; Gyeong Been Lee; Hee-Ryang Kim; In-Soo Cho; Sang-Ho Cha (Veterinary Research Communications, 2016)

Genomic detection and characterization of a Korean isolate of Little cherry virus 1 sampled from a peach tree - Seungmo Lim; Davaajargal Igori; Ran Hee Yoo; Fumei Zhao; In-Sook Cho; Gug-Seoun Choi; Hyoun-Sub Lim; Su-Heon Lee; Jae Sun Moon (Virus Genes, 2015)

Analysis of cytokine production in a newly developed canine tracheal epithelial cell line infected with H3N2 canine influenza virus - Woo-Jung Park; Byung-Joo Park; Young-Jo Song; Dong-Hun Lee; Seong-Su Yuk; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Archives of Virology, 2015)

Dopamine D4 receptors linked to protein kinase G are required for changes in dopamine release followed by locomotor activity after repeated cocaine administration - Jeong Hwan Oh; Dong Kun Lee; Yoon-Bo Shim; In Soo Ryu; Su Yeon Seo; Jieun Kim; Ju Hwan Yang; Hyun-Wook Cho; Eun Sang Choe (Experimental Brain Research, 2015)

MicroRNA expression profiling of p-phenylenediamine treatment in human keratinocyte cell line - Hwa Jun Cha; Ok-Kyu Lee; Soo Yeon Kim; Jung-Min Ko; Su Young Kim; Ji Hye Son; Hyun Joo Han; Shunhua Li; Soo Young Kim; Kyu Joong Ahn; In-Sook An; Sungkwan An; et al. (Molecular & Cellular Toxicology, 2015)

Apoptosis imaging studies in various animal models using radio-iodinated peptide - Wonjung Kwak; Yeong Su Ha; Nisarg Soni; Woonghee Lee; Se-Il Park; Heesu Ahn; Gwang Il An; In-San Kim; Byung-Heon Lee; Jeongsoo Yoo (Apoptosis, 2015)

Isolation and characterization of 12 microsatellite loci from Maackia fauriei (Fabaceae), a large tree endemic to Jeju Island - In-Su Choi; Jung-Hyun Lee; Byoung-Hee Choi (Conservation Genetics Resources, 2014)

Phosphorylation of hypothalamic AMPK on serine485/491 related to sustained weight loss by alpha-lipoic acid in mice treated with olanzapine - Hyunjeong Kim; Minsun Park; Su-Kyoung Lee; Jihyeon Jeong; Kee Namkoong; Hyun-Sang Cho; Jin Young Park; Byung-In Lee; Eosu Kim (Psychopharmacology, 2014)

Erratum to: Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Expression of gibberellin 2-oxidase 4 from Arabidopsis under the control of a senescence-associated promoter results in a dominant semi-dwarf plant with normal flowering - Dong Hee Lee; In Chul Lee; Kook Jin Kim; Dong Su Kim; Hyung Jin Na; In-Jung Lee; Sang-Mo Kang; Hyung-Woo Jeon; Phi Yen Le; Jae-Heung Ko (Journal of Plant Biology, 2014)

Treadmill exercise represses neuronal cell death and inflammation during Aβ-induced ER stress by regulating unfolded protein response in aged presenilin 2 mutant mice - Eun-Bum Kang; In-Su Kwon; Jung-Hoon Koo; Eung-Joon Kim; Chul-Hyun Kim; Jin Lee; Choon-Ho Yang; Young-Il Lee; In-Ho Cho; Joon-Yong Cho (Apoptosis, 2013)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

Identification of molecular mechanism controlling P34 gene expression in soybean - Sung Cheol Koo; Jun Su Seo; Min Jung Park; Hyun Min Cho; Mi Suk Park; Cheol Woo Choi; Wook-Hun Jung; Kyoung Hee Lee; Byung Jun Jin; Seok Hyeon Kim; Sang In Shim; Jung-Sung Chung; et al. (Plant Biotechnology Reports, 2013)

Exploration of Optimal Dosing Regimens of Haloperidol, a D2 Antagonist, via Modeling and Simulation Analysis in a D2 Receptor Occupancy Study - Hyeong-Seok Lim; Su Jin Kim; Yook-Hwan Noh; Byung Chul Lee; Seok-Joon Jin; Hyun Soo Park; Soohyeon Kim; In-Jin Jang; Sang Eun Kim (Pharmaceutical Research, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells - Jae Hyeong Kim; Eun-Kyung Yoon; Hye-Jin Chung; Seong-Yeol Park; Kyeong-Man Hong; Chang-Hun Lee; Yeon-Su Lee; Kyungho Choi; Young Yang; Kyungtae Kim; In-Hoo Kim (Apoptosis, 2013)

Effect of proton beam irradiation on germination, seedling growth, and pasting properties of starch in rice - Sang-Kuk Kim; Shin-Young Park; Kye-Ryung Kim; Jong-Hee Shin; Su-Yong Kim; Hak-Yoon Kim; In-Jung Lee (Journal of Crop Science and Biotechnology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Suppression of NH3 and N2O emissions by massive urea intercalation in montmorillonite - Kwang Seop Kim; Man Park; Choong Lyeal Choi; Dong Hoon Lee; Young Jin Seo; Chan Yong Kim; Jong Su Kim; Seok-In Yun; Hee-Myong Ro; Sridhar Komarneni (Journal of Soils and Sediments, 2011)

Functional expression and magnetic nanoparticle-based Immobilization of a protein-engineered marine fish epoxide hydrolase of Mugil cephalus for enantioselective hydrolysis of racemic styrene oxide - Sung Hee Choi; Hee Sook Kim; In Su Lee; Eun Yeol Lee (Biotechnology Letters, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Effects of Light, Temperature, and Water Depth on Growth of a Rare Aquatic Plant, Ranunculus kadzusensis - In Su Jo; Dong Uk Han; Yong Joo Cho; Eun Ju Lee (Journal of Plant Biology, 2010)

Methyl jasmonate alleviated salinity stress in soybean - Ji Young Yoon; Muhammad Hamayun; Su-Kyung Lee; In-Jung Lee (Journal of Crop Science and Biotechnology, 2009)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Molecular authentication of ginseng cultivars by comparison of internal transcribed spacer and 5.8S rDNA sequences - Ok Tae Kim; Kyong Hwan Bang; Dong Su In; Jei Wan Lee; Young Chang Kim; Yoo Soo Shin; Dong Yun Hyun; Sung Sik Lee; Seon Woo Cha; Nak Sul Seong (Plant Biotechnology Reports, 2007)

Sulindac-derived reactive oxygen species induce apoptosis of human multiple myeloma cells via p38 mitogen activated protein kinase-induced mitochondrial dysfunction - Sung-Keum Seo; Hyung-Chahn Lee; Sang-Hyeok Woo; Hyeon-Ok Jin; Doo-Hyun Yoo; Su-Jae Lee; Sungkwan An; Tae-Boo Choe; Myung-Jin Park; Seok-Il Hong; In-Chul Park; Chang-Hun Rhee (Apoptosis, 2007)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Brain-derived neurotrophic factor modulates the dopaminergic network in the rat retina after axotomy - Eun-Jin Lee; Myoung-Chul Song; Hyun-Ju Kim; Eun-Jin Lim; In-Beom Kim; Su-Ja Oh; Jung-IL Moon; Myung-Hoon Chun (Cell and Tissue Research, 2005)

Phosphoinositide 3-kinase activity leads to silica-induced NF-κB activation through interacting with tyrosine-phosphorylated IκB-α and contributing to tyrosine phosphorylation of p65 NF-κB - Jihee Lee Kang; Hui Su Lee; In Soon Pack; Kyu Chung Hur; Vincent Castranova (Molecular and Cellular Biochemistry, 2003)

Localization of CD15 immunoreactivity in the rat retina - Eun-Jin Lee; Wook-Hyun Shon; In-Beom Kim; Sung-Oh Kwon; Su-Ja Oh; Myung-Hoon Chun (Cell and Tissue Research, 2002)

Decolorization of triphenylmethane and azo dyes by Citrobacter sp. - Sun-Young An; Sang-Ki Min; In-Ho Cha; Yong-Lark Choi; Young-Su Cho; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2002)

Light- and electron-microscopic analysis of neuropeptide Y-immunoreactive amacrine cells in the guinea pig retina - Wha-Sun Kang; Min-Young Lim; Eun-Jin Lee; In-Beom Kim; Su-Ja Oh; Nicholas C. Brecha; Cheol-Beom Park; Myung-Hoon Chun (Cell and Tissue Research, 2001)

Expression and purification of Listeria innocua Sv6b p60 invasion associated protein - Yong-Hee Choi; Sang-Hoon Han; Yong-Soon Lee; Yoon-Kyu Lim; In-Gyu Kim; Byoung-Su Yoon (Biotechnology Letters, 2001)